Interior Design of Batak Cultural Center With The Implementation Of Batak Toba Gorga In Medan City - Stefani Pangaribuan (Faculty Of Arts and Design Sebelas Maret University, 2025)
Traditional culture, including Batak culture, is increasingly being overshadowed by modern influences. Medan City, which has the largest Batak population in Indonesia, still lacks a cultural center that truly represents Batak heritage. Furthermore, the relocation of the North Sumatera Cultural Park to PRSU has resulted in limited accessibility and functionality. To support cultural preservation efforts, establishing a Batak Cultural Center in Medan City is essential. The design of this cultural center incorporates the design programming method by David K. Ballast and the pictorial transformation approach by Anthony Anthodias, adapting the Batak Toba Gorga carvings and the Tiga Bolit color scheme. This cultural center aims to provide a representative space and foster greater appreciation of Batak culture among younger generations.